Developing a Mobile-Assisted Project-Based Learning Model for a Learning Media Course - Batubara, Hamdan Husein; Noor, Hasni; Siregar, Pahri; Ihwanah, Al; Husni, Miftahul; Wibowo, Djoko Rohadi; Maghfurin, Ahmad; Ariani, Dessy Noor (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The ability to create and use effective learning media is critical to students’ academic success. Therefore, a customized learning model for a learning media course needs to be developed to enhance learning effectiveness. The mobile-assisted project-based learning (PjBL) model was developed under the guidance of the Dick and Carey model to improve student learning outcomes in a learning media course. The validity test conducted for this model received a good score from expert validators, with an average score of 4.50 for usability and presentation, 4.56 for display, and 4.53 for language. The effectiveness test showed a high average n-gain of 0.83 in the one-to-one trial, 0.74 in the small group trial, and 0.73 in the large group trial. In addition, student feedback on the practicality of the mobile-assisted PjBL model was very good, with an average score of 4.31, or 86% of the ideal score. Based on these results, it is highly recommended to implement the mobile-supported PjBL model when teaching a learning media course.